Hubungan Pemahaman Konsep dan Kepercayaan Diri Peserta Didik Dengan Kemampuan Mengemukakan Pendapat Pada Materi Ekologi dan Keanekaragaman Hayati Kelas VII SMP Negeri 22 Samarinda - Dilenia Agustin Fajriana; Jailani Jailani; Sri Purwati; Ruqqoyah Nasution (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This study aims to determine the relationship between concept understanding and self-confidence of students with the ability to express opinions on ecology and biodiversity material in class VII SMP Negeri 22 Samarinda. The research method used by researchers is correlation with a quantitative approach. The sampling technique used in this study was simple random sampling with VII B, VII D, and VII E classes as samples. Data analysis techniques using multiple correlation tests. The results of the data analysis obtained show Sig. F Change of 0.000, the value is smaller than 0.05, so Ha is accepted. From these results it can be concluded that there is a significant relationship with a very strong category between concept understanding and self-confidence with the ability to express students' opinions on ecological material and biodiversity in class VII SMP Negeri 22 Samarinda.